2012
DOI: 10.1124/mol.112.081802
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Group I Metabotropic Glutamate Receptors Potentiates Heteromeric Kainate Receptors

Abstract: Kainate receptors (KARs), a family of ionotropic glutamate receptors, are widely expressed in the central nervous system and are critically involved in synaptic transmission. KAR activation is influenced by metabotropic glutamate receptor (mGlu) signaling, but the underlying mechanisms are not understood. We undertook studies to examine how mGlu modulation affects activation of KARs. Confocal immunohistochemistry of rat hippocampus and cultured rat cortex revealed colocalization of the high-affinity KAR subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 56 publications
4
23
1
Order By: Relevance
“…We treated control and tau knockdown neurons with Aβ 42 prior to KA treatment and found that Aβ 42 had a biphasic effect on the KA-induced Ca 2+ cyt response and that this effect was not prevented by the reduction of tau expression. The biphasic effect of Aβ 42 we observed on KA-induced Ca 2+ influx mimics previously demonstrated modulation of KAR by group 1 mGluRs and protein kinase C (PKC) (Cho et al, 2003; Nasu-Nishimura et al, 2010; Rojas et al, 2013). In addition, Aβ has previously been shown to activate group 1 mGluRs and elicit downstream effects on glutamate receptor activity (Um et al, 2012; Um et al, 2013).…”
Section: Introductionsupporting
confidence: 87%
“…We treated control and tau knockdown neurons with Aβ 42 prior to KA treatment and found that Aβ 42 had a biphasic effect on the KA-induced Ca 2+ cyt response and that this effect was not prevented by the reduction of tau expression. The biphasic effect of Aβ 42 we observed on KA-induced Ca 2+ influx mimics previously demonstrated modulation of KAR by group 1 mGluRs and protein kinase C (PKC) (Cho et al, 2003; Nasu-Nishimura et al, 2010; Rojas et al, 2013). In addition, Aβ has previously been shown to activate group 1 mGluRs and elicit downstream effects on glutamate receptor activity (Um et al, 2012; Um et al, 2013).…”
Section: Introductionsupporting
confidence: 87%
“…There was an interesting difference between the findings by Rojas et al (2013) and Cho et al (2003), namely the involvement of Ca 21 mobilization in the regulation of KARs by group I mGlu receptors. In the Cho et al (2003) study the mGlu5-mediated potentiation of (R,S)-2-amino-3-(3-hydroxy-5-tert-butylisoxazol-4-yl)propanoic acid-activated KAR currents was calcium-independent; however, in Rojas et al (2013), the potentiation of heteromeric KARs by activation of group I mGlu receptors was clearly calcium-dependent, as the potentiation was lost in the presence of the calcium chelator 1,2-bis(2-aminophenoxy)ethane-N,N,N9,N9-tetraacetic acid. This difference in the contribution of a critical signaling molecule suggests that there may be multiple pathways regulating KARs following mGlu receptor activation.…”
Section: Kainate Receptorscontrasting
confidence: 44%
“…It was also not clear which subunits of KAR were involved in the modulation. Rojas et al (2013) recently demonstrated the regulation of heteromeric KARs by group I mGlu receptors in cultured cortical and hippocampal neurons and Xenopus oocytes. Pronounced potentiation of heteromeric KAR (consisting of high-and low-affinity subunits) currents was observed following activation of group I mGlu receptors (Fig.…”
Section: Kainate Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like GABA B receptors, the end result of triggering this reaction cascade may be modulation of ionotropic receptors. For example, group I metabotropic glutamate receptors have been shown to be able to potentiate the responses of kainate receptors in the hippocampus and cerebral cortex in rats [37]. The postsynaptic glutamate receptors of cortical pyramidal cells have also been shown to modulate the operation of ionotropic NMDA-type glutamate receptors [6,44].…”
Section: Modulation Of Gaba-andmentioning
confidence: 98%